ANALISIS MATERIALISME BERDASARKAN TINGKAT GENERASI DI KOTA SAMARINDA - Jenita, Mia; Astuti, Ratna Fitri; Ellyawati, Noor; Ruspian, Ruspian (Prodi Pendidikan Ekonomi Universitas Balikpapan, 2026)
Materialism is a perspective that places the ownership of goods as an important part of an individual's life. In the community of Samarinda City, the ownership of goods is often associated with self-esteem, satisfaction, and personal achievement, which allows differences in the level of materialism among generations. This study aims to analyze materialism based on generational levels in Samarinda City and to identify the generation with the highest level of materialism. This research employed a quantitative approach with a descriptive design. The sample consisted of 96 respondents from Baby Boomers, Generation X, Generation Y, and Generation Z, determined using the Lemeshow formula with an incidental sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using descriptive statistics by calculating the mean and percentage. The results show that, in general, the level of materialism among the people of Samarinda City falls into the low category, with 57.29% of respondents categorized as low and 11.46% as very low. However, 29.17% of respondents fall into the high category and 2.08% into the very high category. These findings indicate that the ownership of goods is not the primary basis for the formation of self-identity. Instead, possessions are more often viewed as a source of happiness rather than a means of gaining social recognition. Furthermore, the tendency to accumulate possessions is not particularly strong, indicating that a lifestyle oriented toward excessive ownership is not dominant. Based on generational levels, Generation Z has the highest level of materialism compared to other generations, particularly in interpreting ownership as part of self-identity and a source of happiness.